Dream worlds : mass consumption in late nineteenth-century France - Williams, Rosalind H. (Berkeley ; Oxford : University of California Press, 1991)
In Dream Worlds, Rosalind Williams examines the origins and moral implications of consumer society, providing a cultural history of its emergence in late nineteenth-century France.
1. Implications of the Consumer Revolution -- Part 1. Development of Consumer Lifestyles -- 2. Closed World of Courtly Consumption -- 3. Dream World of Mass Consumption -- 4. Dandies and Elitist Consumption -- 5. Decorative Arts Reform and Democratic Consumption -- Part 2. Development of Critical Thought about Consumption -- 6. From Luxury to Solidarity: The Quest for a Morale of the Consumer -- 7. Charles Gide and the Emergence of Consumer Activism -- 8. Durkheim, Tarde, and the Emergence of a Sociology of Consumption -- 9. Fragment of Future History: Beyond the Consumer Revolution.
JSTOR
Keywords: Consumer behavior -- History; France; Consommateurs -- Comportement -- Histoire; HISTORY / Europe / General; Consumer behavior; France; History